Investigation of Amateur and Professional Athlete’s Novel Coronavirus (COVID-19) Anxiety – Aspect of Managerial Decision - Gümüşgül, Ceren; Ersoy, Adnan; Gümüşgül, Osman (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
Cases because of the Novel Coronavirus (COVID 19), experienced in the sports community, may cause athletes, technical teams, employees, and professionals to experience coronavirus anxiety. Accordingly, this study aimed to examine the anxiety of Novel Coronavirus (Covid-19) in terms of amateur and professional athletes. Two hundred fifty-six active athletes (187 males and 69 females) who studied at the Faculty of Sport Sciences, Kütahya Dumlupinar University, voluntarily participated in this research. The Novel Coronavirus (COVID-19) Anxiety Scale developed by Tekkurşun ve Demir et al. (2020) was used in the research. Parametric tests, as T-Test and One Way ANOVA tests were applied. According to the results, significant differences were determined according to gender, athletes level, roommate during the pandemic (p<0.05). However, according to exercising at home, there was no statistically significant difference following the news of coronavirus in social media and age variables (p>0.05). According to the findings obtained, it is thought that the Novel Coronavirus (Covid-19) anxiety experienced by athletes, whether or not there is a branch of sports that requires contact, will be observed in athletes in different variables and this will be reflected in the preparation process in training and performance in the field and that the athletes may be in aggressive behaviors in psychological pressure. In this process, it was considered essential to examine the athletes’ concerns when deciding to postpone some leagues given by the federations to register or cancel as they did from the pandemic process. In this context, some findings were revealed.